Patterns of Behavior in Biodiversity Preservation - Metrick, Andrew; Weitzman, Martin L. (Washington, DC: World Bank, Policy Research Dept., Environment, Infrastructure, and Agriculture Division, 1994)
Narrowly, this paper is about determining what explains the species-by-species protection and spending decisions of certain relevant U.S. federal and state government organizations.
"September 1994"--Cover.
Includes bibliographical references (p. 26-28).
ne 22/03/2018
Loan
Keywords: Endangered species; Environmental Protection; Biodiversity Conservation; United States